Pour une production de connaissances scientifiques mobilisables dans la pratique de terrain : quels types de dynamiques relationnelles entre chercheurs et praticiens ? - Amélie Turlais
According to the positivist paradigm, the distance between researchers and their object of research is a guarantee of their objectivity, neutrality and autonomy to produce scientific knowledge. However since the seventies, this dualist vision with researchers on one side and social actors on the other side is contested. This article questions how pertinent it might be to consider an axiological neutrality as a necessary condition to the production of scientific knowledge. It will be explained that to produce scientific knowledge which can also be useful to practitioners, it should be taken into account three types of relationships between researchers and practitioners : negotiation, acceptance and reflexiveness.